Analisis Laju Pertumbuhan, Efektivitas, Kontribusi, dan Trend Penerimaan Pajak Daerah dalam Meningkatkan Pendapatan Asli Daerah - Rin Marka, Kemas; Agung Nugroho, Ari; Zukhri, Nizwan (CV. Lafadz Jaya, 2023)
This study aims to see how the growth rate, the effectiveness of collection, its contribution to local revenue and the trend of regional taxes in West Bangka Regency. To obtain the results, several variables were examined, namely PAD, the amount of local tax revenue, the realization of local tax revenue and the target of local taxes. The analysis used in this study is descriptive quantitative analysis, which is used to provide information about each research variable, namely by using research analysis of growth rate, effectiveness analysis, contribution analysis, and trend analysis. While the data on the variables used in this study are secondary data obtained from BP2RD West Bangka Regency for the period 2017-2021. The results of the study show that the average regional tax growth rate for 2017-2021 has not been successful, namely 11.62% per year. Then the average effectiveness level of local tax collection is quite effective, namely 89.92%. Local tax contribution to PAD is quite good with an average of 30.92% per year. Trend analysis in the prospect of local tax revenue for the next five years has increased every year with an average increase of 20% per year.